Assessment of Knowledge Gaps in Cervical Cancer Screening and HPV Vaccination Among Chinese Women: A Comprehensive Population-Based Study - Huang X; Ruan G; Sun P (Cancer Management and Research)
Xinxin Huang,1 Guanyu Ruan,2 Pengming Sun2 1The Ministry of Health, Fujian Maternity and Child Health Hospital College of Clinical Medicine for Obstetrics & Gynecology and Pediatrics, Fujian Medical University, Fuzhou, Fujian Province, People’s Republic of China; 2Laboratory of Gynecologic Oncology, Fujian Clinical Research Center for Gynecologic Oncology, Fujian Matermity and Child Health Hospital College of Clinical Medicine for Obstetrics & Gynecology and Pediatrics, Fujian Medical University, Fuzhou, Fujian Province, People’s Republic of ChinaCorrespondence: Guanyu Ruan; Pengming Sun, Email ruangy_fjsfy@163.com; sunfemy@hotmail.comBackground: While studies on cervical cancer screening (CCS) and human papillomavirus (HPV) vaccine uptake exist in China, few have examined both within populations participating in CCS programs.Methods: This cross-sectional, population-based survey included 37,797 women aged 18– 64 years attending gynecological outpatient clinics. Participants completed a questionnaire assessing CCS awareness and participation. Additionally, HPV vaccine knowledge was investigated in a sub-sample of 17,010 women aged < 45 years.Results: The mean age of participants was 45.06 years (SD: 8.52). The mean CCS knowledge score was 63.13%, with 52.53% reporting prior CCS uptake. Factors associated with lower CCS knowledge included low monthly household income, lack of rural cooperative medical insurance, low literacy, not having received CCS within the past 3 years, unmarried status, and childbirth history. A strong positive correlation was observed between CCS knowledge and adherence to CCS recommendations (Spearman correlation coefficient: 0.708, p < 0.01). Awareness of the HPV vaccine was reported by 48.33% of participants, with HPV vaccine knowledge positively correlated with CCS awareness (Spearman correlation coefficient: 0.629, p < 0.01). CCS knowledge partially mediated the relationship between HPV vaccine knowledge and willingness to vaccinate, with a mediating effect size of 21.16%.Conclusion: Integrated health education efforts targeting CCS and HPV vaccine awareness are essential. Empowering women to understand the significance of HPV vaccination and regular CCS participation can enhance cervical cancer prevention strategies.Keywords: knowledge, cervical cancer, HPV vaccine, screening, mediating effect